Pengaruh Kompensasi dan Lingkungan Kerja Terhadap Semangat Kerja Karyawan pada PT. Bina Sawit Nusantara (BSN) Pekanbaru - Hendra Saputra; Susi Hendriani; Chairul Amsal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aims to determine and analyze the effect of compensation and work environment on employee morale. This study dilakuakan to most employees in the PT. BINA SAWIT NUSANTARA (BSN) Pekanbaru by 67 people. To process the data obtained from the respondents, the authors used SPSS for windows 17:00. The results of this study showed a positive and significant effect of partial and simultaneous independent variable (compensation and work environment) on the dependent variable (employee morale). This can be evidenced by the F test and t test, by looking at the value of F (50 546) > F (2:64) (3.14) with sig (0,000) <0.005. Based on the t test, the t value of compensation (3447) and the work environment of the t (7,001), and the value of t count > t table (1,997). Based on the test results of the coefficient of determination (R2) indicates that the bound variable is affected by the independent variable, the magnitude of these effects was 61.2%. The company is expected to always consider the condition of compensation and work environment of employees, so that employees become excited in the works